Evaluation of bleeding duration and risk between different dual antiplatelet strategies administered after percutaneous coronary intervention: a scoping review (Research, Society and Development, 2023)
Patients with Acute Coronary Syndrome (ACS) require drug-eluting stent implantation after percutaneous coronary intervention (PCI), associated with the administration of dual antiplatelet therapy (DAPT) to reduce the thrombotic risk. Considering the evaluation between ischemic protection and the chance of hemorrhagic events, new TDAP strategies have been used, allowing the prevention of possible harmful outcomes. The present study aims to evaluate the duration and risk of bleeding between different TDAP strategies administered after PCI. For this scope review, carried out through the PubMed and ScienceDirect platforms, between the years 2020 and 2023, the chosen descriptors were: ''Platelet Aggregation Inhibitors'', ''Percutaneous Coronary Intervention'' and ''Hemorrhage''. Inclusion criteria consisted of (1) evaluation of the duration and risk of bleeding in different TDAP strategies (2) analysis between different types of antiplatelet agents (3) studies that addressed follow-up and clinical management (4) articles in English is Portuguese. Exclusion criteria consisted of inappropriateness to the theme, case reports, editorials, simple reviews, animal studies, in addition to texts outside the time limit. Prolonged and long-acting TDAP regimens showed greater ischemic protection and increased risk of bleeding. Short or very short duration regimens were associated with reduced rates of major bleeding, being beneficial to elderly or thrombocytopenic patients. The management of cases with high thrombotic and hemorrhagic risk, as well as the use of predictive scores remain controversial topics to be elucidated through new studies.